An ultralow-charge-overpotential and long-cycle-life solid-state Li-CO2 battery enabled by plasmon-enhanced solar photothermal catalysis. (September 2022) - Wang, Sheng; Song, Hucheng; Zhu, Ting; Chen, Jiaming; Yu, Zhiqian; Wang, Pengfei; Yu, Linwei; Xu, Jun; Zhou, Haoshen; Chen, Kunji
Abstract: Lithium-carbon dioxide (Li-CO2 ) batteries, especially solid-state Li-CO2 batteries, have attracted much attention due to the high energy density and potential application of carbon neutrality. However, the extremely sluggish kinetics of CO2 evolution reaction in the batteries result in a notorious high-charge-potential over 4.0 V, thus impeding the development of Li-CO2 batteries. Here, by in-situ constructing a plasmonic Ru/Li2 CO3 -based heterostructure, we report an ultra-low charge overpotential and long cycle life solid-state Li-CO2 battery via the energetic hot carries produced by nonradiative decay of localized surface plasmons where solar energy can be efficintly harvested (over 90% absorption efficiency from 200 nm to 1000 nm), concentrated and converted on the plasmonic Ru catalysts. Experimental results show that the plasmonic photothermal catalysis using Ru catalysts can catalyze C-O bond cleavage and construct a plasmonic Ru/Li2 CO3 -based heterostructure in the battery on discharge, and effectively accelerate the CO2 envolution reaction via injecting the hot carriers generated from the plasmonic Ru catalysts into the discharged Li2 CO3 -based products on charge. As a result, by using a chemically stable and high Li-ion conductive MSI layer, the battery shows a record low charge potential (2.99 V) even after a long-term cycling (over 450 cycles) operating at 500 mA g −1 at 500 mAh g −1 . This battery technology paves the way for developing next-generation high-specific-energy Li-CO2 batteries with carbon neutrality. Graphical Abstract: By in-situ constructed plasmonic Ru/discharged products heterostructure, a record low-charge-potential ( 2.95 V) and long-cycle-life solid-state Li-CO2 battery via the energetic hot carries produced by nonradiative decay of localized surface plasmons where solar energy can be efficintly harvested (>90% absorption from 200 nm to 1000 nm), concentrated and converted on the plasmonic Ru catalysts assembled on CNF gas diffuction layer. ga1 Highlights: In-situ constructed plasmonic Ru/Li2 CO3 -based heterostructure on discharge. The heterostructure construction consisting of plasmonic Ru and discharged Li2 CO3 products. Hot carrier generation and injection in the plasmonic heterostructure. The battery demonstrates a record ultra-low charge potential (<3.0 V) and outstanding cycle stability even after 450 cycles.